Does Working Capital Efficiency Drive Profitability? Evidence from a Listed Telecommunications Company - Rahmawati; Rachmawati Kadir; Andi Naila Quin Azisah Alisyahbana (Global Research Collaboration, 2025)
This study examines the association between working capital turnover and profitability in a publicly listed telecommunications company over 2018–2024, spanning pre-pandemic (2018–2019), pandemic (2020–2021), and post-pandemic (2022–2024) phases. Using secondary data from audited annual financial statements and stock-exchange filings, the analysis applies ratio and trend techniques to assess how liquidity management relates to earnings performance amid shifting demand and investment cycles. The results indicate an inverse pattern: periods of higher working capital turnover did not coincide with higher profitability, while lower turnover was accompanied by improved profitability. This outcome aligns with the sector’s capital-intensive, subscription-driven cash cycle, where rapid turnover can reflect tighter working capital positions that constrain service quality and margin capture, whereas more moderate turnover is consistent with capacity expansion, disciplined receivables management, and stronger margins. The pandemic and its aftermath amplified these dynamics as surging data usage, network investments, and pricing pressures reshaped short-term liquidity needs and returns. The study contributes sector-specific evidence on liquidity–profitability trade-offs across a systemic shock and underscores that accelerating working capital turnover is not universally profit-enhancing in telecommunications. Managerially, the findings point to calibrating working capital policies to demand volatility, maintaining liquidity buffers, and aligning receivables and “inventory-like” network capacity with profitability targets.